Key audit matters, audit partner tenure and audit reporting lag: Evidence from Malaysia - Khoo, Vivian (2019)
Audit timeliness is one of the most important factors that determine timeliness of financial reporting. Undue delay in audit report would cause delay in financial reporting and consequently affect decision making of the users of financial statement. This study investigates the relationship between Key Audit Matters (KAM) category, which has longer audit reporting lag (ARL) and ARL. This study also examines the moderating effect of audit partner tenure on the relationship between KAM category, which has longer ARL and ARL. The data was collected from 395 companies with financial year end of 31 December 2016 listed on Bursa Malaysia Main Board. The sample was approximately 50 percent from the population of total 795 companies. Descriptive statistics showed that on average, the companies took approximately 92 days to complete their audit report. From mean t-test analysis and univariate analysis, KAM category-receivables was found to be positive and statistically significant in predicting ARL. Using ordinary least squares regression analysis, it was found that KAM category-receivables has a positive and significant relationship with ARL. However, audit partner tenure did not moderate the KAM category-receivables-ARL relationship. Further analysis suggested the potentiality of long-tenured audit partners from Big 4 to reduce ARL. The study shall be interest of the auditors, regulators and management of companies. The findings of the study would help auditors in developing a more realistic audit strategy and alleviate Bursa Malaysia’s investigation and enforcement actions, other than serving as a justification basis of regulation reformation in the future. The findings of the study also contribute to the management of companies in developing comprehensive internal audit strategic plan and deploying resources to minimise ARL.